A data-driven approach exploring the entrepreneurial-managerial spectrum - Alexa Booras; Jan Auernhammer; Katerina Monlux; Jennifer Bruno; Sahar Jahanikia; Hua Xie; Neeraj Sonalkar; Manish Saggar (Frontiers in Organizational Psychology)
Entrepreneurs are responsible for starting new ventures, often with high risk and innovation, while managers oversee existing organizations, optimize operations, and achieve predefined goals. Although frequently seen as a dichotomy, entrepreneurs and managers share responsibilities for building and sustaining a business, and hence, this could also be studied as a spectrum. Previous research has individually examined specific aspects of entrepreneurial (vs. managerial) work, but limited studies have examined their effects holistically. Using a wide range of survey instruments, we took a data-driven approach to explore the entrepreneurial-managerial spectrum. Exploratory factor analysis revealed five latent factors driving variance in our data: Negative Emotions, Fulfillment and Support, Creative Capacity, Collaborative Personality, and Decision-Making Avoidance and Hypervigilance. When analyzed as a traditional dichotomy, we found that entrepreneurs scored lower than managers in Decision-Making Avoidance and Hypervigilance, and Collaborative Personality. As a spectrum, data suggested (1) an increase in Creative Capacity with more entrepreneurial experience and (2) a decrease in Decision-Making Avoidance & Hypervigilance with more entrepreneurial experience. On the other hand, emotional health and career success remained similar across groups. Overall, we explored the complex profile of entrepreneurs and managers as a step toward understanding the dynamic and unique combination of personality, cognition, and emotional health across the entrepreneurial-managerial spectrum. Our study provides a first step toward an integrative lens through which future work can extend to develop programs that improve entrepreneurial decision-making and creativity, with practical implications for organizational behavior, leadership development, and cultivating entrepreneurial mindsets within existing organizations.